PENGARUH PEMBIAYAAN MUDHARABAH DAN PEMBIAYAAN MUSYARAKAH TERHADAP TINGKAT PROFITABILITAS PADA PT BANK MUAMALAT INDONESIA Tbk. PERIODE 2008 – 2017 - M. Givi Elgivia; Mufid Habib Mustofa; Maya Insa Fiana (DIRHAM Jurnal Ekonomi Islam, 2020)
Financial Institutions In Particular The Banking Sector Is A Community Institution Expected To Be Able To Control The Economic Wheel. Countries Of Indonesia As A State That The Majority Of Islamic Religion Has Longly Taken The Presence Of The Financial Institution System Which According To The Needs Of The Needs Is Not Financial, But Also The Morality Demands. Islamic Bank. Methods Used In Writing Reports Final This Is Using Analysis Descriptive, Where The Method Of Data Collection To Do With How To Give A Snapshot, Explanation Systematic, Factual And Accurate To Object That Is The Subject Issues Is The Effect Of Financing Mudharabah And Musyarakah On The Level Of Profitability In Pt. Bank Muamalat Indonesia Tbk Period 2008 – 2017 Based On These Research Results Show The Value Of Determination Coefficients (R2) That Financing Mudharabah And Musyarakah Gives 40% Diversity To The Profitability Level, As Well As A 60% Rate, Is Affected By Other Factors Not Observed In This Research.